Forget you - Echols, Jennifer (New York : Gallery Books MTV Books, 2010)
After her parents separate, seventeen-year-old Zoey has a car accident she cannot remember and starts asking her high school swim team friends what happened on that night at the beach on the Florida panhandle.
Keywords: Conduct of life -- Juvenile fiction; Traffic accidents -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Swimming -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Florida -- Juvenile fiction